Resilience and Green Spaces: Association with Stress among Contact Centre Workers in the Philippines - Villanueva, Celine P. (Archīum Ateneo, 2023)
Issue Addressed Philippine contact centres are rife with factors that contribute to work-related stress; health promotion strategies are needed to mitigate the impacts. With a transactional framework with the environment, this study examined the relationship of stress with resilience and the presence of urban green spaces (UGS) in the environment, while accounting for individual characteristics (ie, age, household income, exercise frequency). Methods: Participants include employees (Stage 1 N = 186; Stage 2 N = 89) from six contact centres in the capital region of the Philippines. A two-stage online survey included standardised instruments to measure stress (10-item Perceived Stress Scale) and resilience (Connor-Davidson Resilience Scale), customised questions to gather demographic information and probe on participants' insights. Google Earth Pro was used for satellite mapping of UGS, followed by on-site ocular inspection. Results Participants' average stress level was categorised as high; primary stressors included client demands and workload. The objectively measured percentages of UGS in the study sites' vicinity were categorised as low. Participants found UGS visible after careful observation, and majority were aware of UGS in their workplace vicinity. Resilience, household income and awareness of UGS in the vicinity significantly predicted stress levels. Conclusion Contact centre workers experienced high stress levels and their workplaces had little accessible UGS. Resilience, household income and awareness of UGS are significant contributors to stress levels. So What? Health promotion in Philippine contact centres could consider strategies that include building resilience, enhancing income security and promoting the awareness of UGS within the workplace vicinity.